2007
DOI: 10.1152/ajprenal.00124.2007
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone receptor antagonism alleviates proteinuria, but not malignant hypertension, in Cyp1a1-Ren2 transgenic rats

Abstract: The contribution of elevated aldosterone to the pathogenesis of malignant, ANG II-dependent hypertension remains uncertain. Therefore, we examined whether chronic mineralocorticoid receptor blockade attenuates the development of malignant hypertension in transgenic rats (TGRs) with inducible expression of the Ren2 gene [TGR(Cyp1a1Ren2)]. Systolic blood pressure (SBP) was measured by radiotelemetry in male TGRs in three groups: 1) control (n = 9), 2) hypertensives (HT; n = 8), and 3) hypertensives + spironolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 37 publications
11
36
0
Order By: Relevance
“…14,15 Antagonism of the mineralcorticoid receptor (MR, aldosterone receptor) reduces proteinuria and kidney tubulointerstitial fibrosis, independent of changes in blood pressure. [16][17][18][19] In cell culture, aldosterone can activate the Rho kinase pathway, and the Rho kinase pathway is likely responsible for the profibrotic actions of aldosterone in renal proximal tubular epithelial cells via inducing epithelial-mesenchymal transition and extracellular matrix excretion. 20 MR antagonism improves proximal tubule integrity by targeting mammalian target of rapamycin (mTOR)/S6 kinase 1 (S6K1) signaling and redox status independent of changes in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Antagonism of the mineralcorticoid receptor (MR, aldosterone receptor) reduces proteinuria and kidney tubulointerstitial fibrosis, independent of changes in blood pressure. [16][17][18][19] In cell culture, aldosterone can activate the Rho kinase pathway, and the Rho kinase pathway is likely responsible for the profibrotic actions of aldosterone in renal proximal tubular epithelial cells via inducing epithelial-mesenchymal transition and extracellular matrix excretion. 20 MR antagonism improves proximal tubule integrity by targeting mammalian target of rapamycin (mTOR)/S6 kinase 1 (S6K1) signaling and redox status independent of changes in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the Ren2, as well as the Cyp1a1-Ren2, suggests that MR antagonism leads to improvements in glomerular damage and proteinuria without reductions in SBP [7,30]. Recent work from our group and others suggest that at early stages of kidney injury there are urine protein contributions derived from either impairments in megalin-mediated endocytosis or the degradation process in PTCs [31,36].…”
Section: Discussionmentioning
confidence: 99%
“…MR-dependent changes in kidney function are thought to largely occur through non-genomic actions including generation of oxidative stress and impairments in metabolic signaling pathways in models of chronic pressure overload [1,2,5]. In this context, recent data highlight a role for antagonism of the MR in reducing proteinuria and kidney tubulointerstitial fibrosis, independent of changes in blood pressure [1,2,5,6,7]. It has been suggested that these blood pressure-independent anti-fibrotic effects of MR antagonism are mediated, in part, through correction of abnormalities in metabolic signaling pathways [8].…”
Section: Introductionmentioning
confidence: 99%
“…Radiotelemeters (PA-C40; DSI, St. Paul, MN) were surgically implanted in the abdominal cavity with the catheter end inserted into the descending aorta and fixed in place with a nylon patch and surgical adhesive (39,40). Animals were allowed 5 days to recover from the surgery before initiation of the study.…”
Section: Methodsmentioning
confidence: 99%